LANDSCAPE ECOLOGY OF ENDEMIC BLACK-WINGED STARLING Acridotheres melanopterus tricolor (HORSFIELD, 1821) RELATED TO ENVIRONMENTAL FACTORS IN A TROPICAL SAVANNA OF INDONESIA - Andriwibowo Andriwibowo; Katherine Hedger; Adi Basukriadi; Erwin Nurdin (ZOO INDONESIA, 2022)
The black-winged starling (Acridotheres melanopterus tricolor) is a bird species in Southeast Asia, and this species still exists within Indonesia's tropical savanna landscape. This study aims to estimate the population density of the A. m. tricolor and to model the relationship between this species density and its environmental factors in several land cover types in the Baluran National Park savanna landscape in Java. The environmental factors were Normalized Difference Vegetation Index (NDVI), land cover size, and distance to river obtained from Landsat 8 Operational Land Imager (OLI) and analyzed using Geographical Information System (GIS). General Additive Models (GAM) combined with Principal Component Analysis (PCA) was used to analyze the correlation of bird density with environmental factors. Based on the results, the average density of the A. m. tricolor was eight (8) inds./km2. The correlation model showed a significant positive relationship between bird density and NDVI and a significant negative relationship for distance to river factors, while land cover size did not significantly correlate with the bird density. These findings suggest that vegetation and access to water sources remain a relatively important environmental factors for supporting A. m. tricolor populations and this species conservation in the tropical landscape. The novelty of this research is satellite imagery and GIS usage to elaborate the landscape and habitat of A. m. tricolor. In addition, this study also contributes to modelling the most overarching environmental factors of A. m. tricolor in Indonesia's tropical savanna landscape.